Nota técnica 1: The existence of compensated equilibrium - López, Augusto (Estudios de Economía, 2016)
The purpose of this note is twofold. First and foremost, we wish to make Arrow and Hahn’s proof of the existence of compensated equilibrium a little less mysterious by expanding and elucidating upon the various interconnecting steps presented in the text and then we wish to present proofs of some important theorems of topology which the authors use and which, I presume, the general reader does not find so obvious.